2015
DOI: 10.1016/j.jaap.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic pyrolysis of waste plastic from electrical and electronic equipment

Abstract: Plastic waste collected from waste electrical and electronic equipment (WEEE) was pyrolysed in the presence of zeolite catalysts to produce a gasoline range aromatic oil. The plastic was from equipment containing cathode ray tubes (CRTs) and also plastic waste from refrigeration equipment. In addition, for comparison the main plastics contained in the WEEE, in the form of high impact polystyrene (HIPS) and acrylonitrile-butadiene-styrene (ABS) were also pyrolysed in the presence of the zeolite catalysts. Two z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 22 publications
(33 reference statements)
3
43
0
Order By: Relevance
“…Despite the heterogeneity of the investigated WEEE, it can be observed that the values reported in this work fall within the range of those reported by various authors. It must be emphasized that in most studies reported in the literature which deal with processes development rather than analytical methods, XRF used for screening or semi-quantitative analysis [9], and IC [35,[39][40][41] are the most used techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the heterogeneity of the investigated WEEE, it can be observed that the values reported in this work fall within the range of those reported by various authors. It must be emphasized that in most studies reported in the literature which deal with processes development rather than analytical methods, XRF used for screening or semi-quantitative analysis [9], and IC [35,[39][40][41] are the most used techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Aguado et al (2007) also conducted a thermal gravimetric analysis (TGA) to evaluate the activity of catalysts by determining the degradation temperature shifts. Without the presence of catalyst, the LDPE started degradation at 419 o C. Employing n-HZSM-5 catalyst, reduced the degradation temperature to 396 o C. Muhammad et al (2015) pyrolysed WEEE in the presence of ZSM-5 and Y-zeolite catalysts using a fixed bed two-stage batch reactor with the plastic pyrolysed in the first stage and the evolved pyrolysis gases catalysed in the second stage reactor for further upgrading and cracking. The main plastics contained in the WEEE were high impact polystyrene (HIPS) and acrylic butadiene styrene (ABS) and were treated in the presence of the zeolite catalysts.…”
Section: Presence Of Catalysts and Effect On Pyrolysismentioning
confidence: 99%
“…Electronic waste represents around 8% of the urban waste volume worldwide 2 . In Europe about 10 million tons WEEE are produced each year 3 and it is estimated that by 2020 the amount generated will reach a total annual tonnage of 12.3 million 4 . Since many times fixing devices is not economically feasible, old electronics are discarded in large quantities.…”
Section: Introductionmentioning
confidence: 99%